Penggunaan Metode Mentoring dan Coaching Model TIRTa untuk Peningkatan Kompetensi Guru dalam Menyusun Modul Ajar - Astuti Triasmani; Hery Winoto Tj; Takim Andriono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Teacher competence in developing learning module in the current implementation of the Independent Curriculum is very important because learning module determines the learning quality in the classroom. This School Action Research aimed to increase the competency of teachers at Kalam Kudus Christian Junior High School in developing learning module using Mentoring Method and TIRTa Model Coaching Methods, with three recipients who were teaching in grades VII and VIII. The researcher used learning modules as the assessed product and observed the teachers’ competence from both pedagogical and professional aspects. The result was very encouraging because it was found that: (1) the subjects got better understanding of the components in the learning module according to its standards; (2) the subjects were able to compose better quality of learning module; (3) the subjects’ pedagogical and professional competence increased; (4) The TIRTa model was very effective for mentoring and coaching since it built the subjects’ awareness of setting goals, identifying strengths and weaknesses, making action plans, and taking responsibility for their plans. This success was shown in the result that the competence of three subjects in the pre-cycle belonged to poor category (< 71), but of cycle I the two subjects got poor category and the other one got average category, and at the end of cycle II all of the subjects changed to good (81 -90).